Possibilities for Developing Intercultural Competence in Language Teaching in Primary School (Using the Example of Selected Material for the 6th Grade) - Zemljak Jontes, Melita (ZORA 160: Imenitnost slovenščine sto let po Pleteršniku, 2026)
The paper presents an analysis of the representation of intercultural and multilingual competence in the Slovene education system from the perspective of content and objectives in the curricula (2018 and 2025) for the 6th grade in the subject Slovene in primary school, and from the perspective of the representation of ma-terials in the selected textbook Slovenščina v oblaku. Samostojni delovni zvezek za slovenščino v 6. razredu osnovne šole with a presentation of possibilities for further discussion.